Prava simetrična verižnica - Razpet, Marko (Obzornik za matematiko in fiziko, 2010)
By using the calculus of variations, we derive the equation of symmetric catenary in the radial gravitational field. Some properties of the obtained curve are also given.
Keywords: matematika; simetrična verižnica